2022
DOI: 10.21608/ejar.2022.118682.1201
|View full text |Cite
|
Sign up to set email alerts
|

Role of Environmental Conditions on Epidemics of Wheat Yellow Rust in Gharbia Governorate, Egypt.

Abstract: This work aimed to evaluate one hundred and fifty-five commercial wheat fields including six varieties of yellow rust (stripe rust) epidemics caused by Puccinia striiformis f. sp. tritici, in Gharbia governorate during the 2019 to 2021 seasons. Also, study the weather variables associated with yellow rust outbreaks in wheat. Temperature, relative humidity, and rain variables were obtained from the regional climate model imeto2 (http//meto.at/farmview/) as well as the World Climate Research Programme (WCRP) Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The high temperature in the disease recording year did not favor the disease. According to recent studies it was confirmed that the most convincing factor for the progression of disease was the temperature in January and February (Elshamy et al, 2022). Another finding suggested that progression of yellow rust was slowed down by temperatures above 23°C (Chakraborty et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The high temperature in the disease recording year did not favor the disease. According to recent studies it was confirmed that the most convincing factor for the progression of disease was the temperature in January and February (Elshamy et al, 2022). Another finding suggested that progression of yellow rust was slowed down by temperatures above 23°C (Chakraborty et al, 2011).…”
Section: Discussionmentioning
confidence: 97%